Pemilihan Teknologi Daur Ulang Effluent Limbah Cair Rumah Sakit Untuk Memenuhi Kebutuhan Air Bersih Pertamanan Dan Kegiatan Non-Potable - Novalina Annisa Yudistira; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Conservation of water resources need to be carried out by large-scale water users, such as hospitals. One of the conservation efforts is recycling wastewater. Recycled water can be used to fulfill the needs of landscape irrigation and non-potable activity in hospital. The one of methods for wastewater recycling design is selecting of alternative technology and processing. Several things which need to paid